Assessing the Environmental Impacts of Alluvial Gold Mining in Betare-Oya, Cameroon (2021–2025): An Integrated Remote Sensing and Ground-Truthing Approach - Zoum, Fon Alain; Fava, Salvatore; Morelli , Davide; Lika Ndimungiang, Bechan (New Countryside, 2025)
Alluvial gold mining in Betare-Oya, Cameroon, poses a significant environmental threat, leading to deforestation, land degradation, and water pollution. This study investigates the spatiotemporal environmental impacts of alluvial gold mining in Betare-Oya, East Cameroon, over the period 2021 to 2025 by integrating remote sensing techniques with field based observations. Sentinel-2 satellite imageries were analyzed using key indices: Bare Soil Index (BSI), Normalized Difference Vegetation Index (NDVI), and Land Use/Land Cover (LULC) to detect land degradation, vegetation loss, and changes in surface conditions. Key results include a substantial increase in bare soil (BSI rising from 19.20% in 2021 to 38.23% in 2024), a decline in dense vegetation (NDVI decreasing from 46.13% in 2021 to 42.34% in 2024), and a conversion of forested areas to mining zones (LULC showing a decrease in dense vegetation from 38.27% in 2021 to 30.69% in 2024, and an increase in bare land from 32.22% to 45.48%). Change detection analysis revealed that the most significant changes are from dense vegetation to bare land and mine sites. Field observations corroborated these findings, highlighting deforestation, soil erosion, and water pollution. While these results demonstrate a strong correlation between mining and environmental degradation, limitations in temporal resolution, spatial resolution, and the scope of ground-truthing necessitate further investigation. Future research should focus on quantifying the specific impacts of artisanal versus semi-mechanized mining, assessing water quality parameters, and evaluating the long-term ecological consequences. This study underscores the urgent need for improved regulation and sustainable management of mining operations to mitigate the negative environmental impacts in Betare-Oya and similar regions.